Arthur Schopenhauer: an underappreciated philosopher in psychiatry and his applied epistemology of body and self- experience - Daub, Jonas; Brandt, Geva A.; Volkmer, Sebastian; Northoff, Georg; Hirjak, Dusan (Schizophrenia research, 2024)
Background - Arthur Schopenhauer (1788-1860) was one of the most important thinkers of the 19th century. Although his writings have exerted great influence in many different disciplines, his epistemological concepts and analysis of the body and self-experience were rarely considered in the context of psychiatric research of schizophrenia spectrum disorders (SSD) and depression (MDD). - Methods - The method applied for the study of anomalous self and body-experience first consists in the close reading and analysis of Schopenhauer's most influential writings, namely his opus magnus “The World as Will and Representation” and his dissertation “On the Fourfold Root of the Principle of Sufficient Reason”. Second, psychopathological and phenomenological aspects of the anomalous body and self, as well as altered space and time experience, are discussed by means of Schopenhauer's philosophy and four patient cases. - Results - Schopenhauer's insights contribute to contemporary psychiatry by (1) unifying materialistic (neurobiological) and idealistic (subjective) conceptions of psychiatric disorders and improving the awareness of methods in psychiatric research; (2) emphasizing the integral significance of the body as a gateway to the surrounding world and basal self-experience; (3) delineating subjective space and time-experience as crucial dimensions of the conditio humana in SSD and MDD; and (4) demonstrating the feasibility of transferring his theories directly to clinical case vignettes stemming from the daily clinical routine. - Conclusion - Close reading of Schopenhauer's texts might help bridge the gap between different scientific methods in psychiatry and overcome the translational crisis of contemporary psychiatry by unifying neurobiological and subjective approaches to SSD and MDD.
Online verfügbar: 30. April 2024, Artikelversion: 17. Mai 2024
Gesehen am 08.10.2024